Screening for active and latent tuberculosis among asylum seekers in Italy: A retrospective cohort analysis. Issue 27 (January 2019) - Pontarelli, Agostina; Marchese, Valentina; Scolari, Carla; Capone, Susanna; El-Hamad, Issa; Donato, Francesco; Moioli, Rolando; Girardi, Enrico; Cirillo, Daniela Maria; Castelli, Francesco; Matteelli, Alberto
Abstract: Background: The World Health Organization conditionally recommends systematic screening of tuberculosis (TB) and Latent Tuberculosis Infection (LTBI) among asylum seekers (AS) from high-burden countries, but the effectiveness of different screening approaches is controversial. Methods: We report the results of a retrospective cohort analysis of TB and LTBI screening among consecutive AS in Brescia, Italy during 2015–2016. TB screening was based on symptoms, LTBI screening on the tuberculin skin test (TST). Logistic regression analysis was performed to identify factors associated with screening uptake. Results: Of 2904 registered AS 2567 (88.4%) were evaluated for TB, 62 (2.4%) had symptoms and active TB yield was 155/100, 000. Prevalence and incidence TB rates were 545/100, 000 persons and 220/100, 000 person-years. Questionnaire screening identified 28.6% (4/14) prevalent cases. Of 2303 (89.7%) AS with TST result, the positivity rate was 36.6% (843/2303). Of the 843 candidates for LTBI treatment 413 (49.0%) completed the screening. LTBI treatment was prescribed to 190 (47.9%) of 397 eligible individuals, 10.8% (91) completed treatment. Conclusions: TB prevalence and incidence rates were high in this AS population, but symptom-based screening performed poorly. LTBI cascade losses were significant and mainly attributable to the defragmentation of the health care system.